Effect of some Bacterial Bioagents against Root-Knot Nematode (Meloidogyne incognita race2) - Devi, Gitanjali; Bora, L.C. (International Journal of Environment, Agriculture and Biotechnology, 2019)
The effect of culture filtrate of different bacterial isolates on egg hatching and juvenile mortality of root-knot nematodes (Meloidogyne incognita race 2) was studied in vitro and the effective strains were selected. The per cent mortality and hatching inhibition was proportional to the concentration of culture filtrate and the duration of exposure period. Culture filtrate of all the isolates of bacteria significantly induced mortality and inhibition of egg hatching of M. incognita juveniles. The highest percentage of inhibition of egg hatching was recorded for Bacillus thuringiensis followed by Bacillus sp. and Pseudomonas fluorescens whereas the highest percentage of mortality of juvenile was recorded for Bacillus thuringiensis followed by Pseudomonas fluorescens and Pseudomonas sp.